Ethics and Consultancy: European Perspectives
IX, 285 p.
Keywords: The present volume in a series of books produced from European Business Eth ics Network (EBEN) conferences in Europe, is a compilation of plenary speeches and papers presented at the 1993 EBEN conference in Oslo, Norway. The theme of this year's conference was "The Use of Consultancy: Ethical Demands and Require ments" and there was a special focus on Eastern Europe. Of over 40 papers present ed at the conference from 165 participants representing 23 countries, we present here 20 selected by the editors as providing an overview of the latest thinking from both academicians and practitioners on the subject of ethics in consulting. Due to strict constraints on space in this volume, several valuable papers presented at the conference must be published elsewhere. We have also tried to maintain the unique flavor of the papers by authors whose mother tongue is not English. The consulting profession is booming in Europe, both in the West and in the for mer Communist Bloc countries. However, it has not previously been subjected to rigorous scrutiny from the ethical point of view. The conference planning commit tee thus sought to put the spotlight on the spreading phenomenon of buying and selling consultancy services within the European Union, within Europe and with the new Eastern Europe. The conference addressed several ethical challenges facing either the buyers or providers of consultancy services in both the private and public sectors.